MODEL PEMETAAN RISIKO KEKERINGAN DI KABUPATEN BIMA, NUSA TENGGARA BARAT - Faizah, Nuraimmatul; Buchori, Imam (Magister Pembangunan Wilayah dan Kota,Undip, 2019)
Drought in Bima regency is an annual phenomenon that always happens every year and its handling is still short-term. Therefore, there needs to be a monitoring and analysis of the drought risk factors so the drought risk mapping can be conducted to plan the drought mitigation. This research aims to develop the drought risk mapping model with Geographic Information System to find out the drought risk level in Bima regency based on the relevant variables. The drought risk model used as the basic of the research is the intersection between hazard and vulnerability, which are the basic models in disaster risk study. This research uses spatial approach with quantitative method which uses statistic indicator to measure and compare several variables. The data was collected by using institutional and literature survey. The data used was secondary data. The data analysis technique used was scoring analysis, weighting, and map overlay. The result of drought risk mapping model in Bima regency was classified into 5 classes, dominated by the Middle Class. The width of the classes consequently from the highest to the lowest are: Middle ±223.232,40 ha, Middle Lower ±136.414,29 ha, Middle High ±47.971,49 ha, Low ±10.962,28 ha dan High ± 1.776,53 ha. Then the model validation was conducted through field survey, with the validity result at 83,61%. The result shows that the modeling was good enough in analyzing the drought risk spatially. For further development, it is recommended to notice the used risk model, data using, analysis unit for each parameter, and the validation that will be used.